Transcriptomics, Targeted Metabolomics and Gene Expression of Blackberry Leaves and Fruits Indicate Flavonoid Metabolic Flux from Leaf to Red Fruit - Gutierrez, Enrique; García-Villaraco, Ana; Lucas, José A.; Gradillas, Ana; Gutierrez-Mañero, F. Javier; Ramos-Solano, Beatriz (Frontiers in Plant Science, 2017)
Blackberries (Rubus spp.) are among the high added value food products relevant for human health due to the increasing evidence of the beneficial effects of polyphenols, which are very abundant in these fruits. Interestingly, these compounds also play a role on plant physiology, being especially relevant their role in plant defense against biotic and abiotic stress. Hence, we hypothesize that since blackberry fruits have high amounts of flavonols and anthocyanins, leaves would also have high amounts of these compounds, and can be studied as a source of active molecules; furthermore, leaf synthesis would support their high contents in fruits. To explore this hypothesis, the present study reports a de novo transcriptome analysis on field grown blackberry leaves and fruits at the same time point, to establish the metabolic relationship of these compounds in both organs. Transcripts were aligned against Fragaria vesca genome, and genes were identified and annotated in different databases; tissue expression pattern showed 20,463 genes common to leaves and fruits, while 6,604 genes were significantly overexpressed only in fruits, while another 6,599 genes were significantly overexpressed in leaves, among which flavonol-anthocyanin transporter genes were present. Bioactives characterization indicated that total phenolics in leaves were three-fold, and flavonols were six-fold than in fruits, while concentration of anthocyanins was higher in fruits; HPLC-MS analysis indicated different composition in leaves and fruits, with cyanidin-3-glucoside as the only common compound identified. Next, RT-qPCR of the core genes in the flavonol anthocyanin pathway and regulatory MYB genes were carried out.. Interestingly, genes in the flavonol-anthocyanin pathway and flavonol-transport families were overexpressed in leaves, consistent with the higher bioactive levels. On the other hand, transcription factors were overexpressed in fruits anticipating an active anthocyanin biosynthesis upon ripening. This suggests that, in addition to the biosynthesis taking place in the fruits during ripening, translocation of flavonols from leaves to fruits contributes to the high amounts of bioactives starting to accumulate in fruits.